Mechanical transmission of lumpy skin disease virus by stomoxys spp (Stomoxys calsitrans, stomoxys sitiens, stomoxys indica), diptera: Muscidae - Issimov, A.; Kutumbetov, L.; Orynbayev, M. B.; Khairullin, B.; Myrzakhmetova, B.; Sultankulova, K.; White, P. J. (Animals. - 2020., 2020)
Samples collected for PCR from recipient animals tested positive in 5 out of 6 cases, while the virus was isolated from 4 of 6 animals. The clinical signs exhibited by recipient animals were mostly moderate in nature with only one severe case. To our knowledge, this is the first time that transmission of LSDV by three Stomoxys species has been demonstrated, and their role as mechanical vectors of LSDV is indicated. Образцы, собранные для ПЦР у животных-реципиентов, дали положительный результат в 5 из 6 случаев, в то время как вирус был выделен у 4 из 6 животных. Клинические признаки, проявляемые животными-реципиентами, были в основном умеренными по своему характеру, только в одном тяжелом случае. Насколько нам известно, это первый раз, когда была продемонстрирована передача LSDV тремя видами Stomoxys, и указана их роль как механических переносчиков LSDV.
Keywords: импакт-фактор 2020; скопус; scopus; web of sciense; зарубежные авторы; научный журнал; периодическое издание; дальнее зарубежье; болезни кожи